2022
DOI: 10.3390/educsci12070471
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Education as a Tool of Promoting Quality in Education: Teachers’ Perception of the Educational Inclusion of Students with Disabilities

Abstract: Teachers’ attitudes towards inclusion are influenced by factors such as training and teaching experiences. However, there is no conclusive trend correlating specific factors with negative or positive attitudes. The aim of this study is to understand the reality of inclusion in schools in Extremadura, Spain, from the teachers’ point of view. To do so, a reliable and valid questionnaire was administered to a total of 106 teachers from more than 20 schools in Extremadura, followed by the subsequent categorization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Thus, there are teachers who have a positive perception of the term "educational inclusion" compared to other teachers who are unfamiliar with the subject but are willing to maintain and improve the educational quality of students with special abilities. This assessment is very important to create plans and ensure good educational quality [24] at local, national and international levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there are teachers who have a positive perception of the term "educational inclusion" compared to other teachers who are unfamiliar with the subject but are willing to maintain and improve the educational quality of students with special abilities. This assessment is very important to create plans and ensure good educational quality [24] at local, national and international levels.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of online education has caused apprehension among many parents who care for their children with special abilities because in countries such as Cuba the policies are consistent with their actions because the role of the teacher is of utmost importance to improve the quality of education [22,23] which is lacking in other countries such as Peru. The factors of influence towards educational inclusion on the part of teachers are their own experience and training [24] . This aspect is highly important for providing a quality education to students with special abilities.…”
Section: Justification and Objectives Of The Researchmentioning
confidence: 99%
“…A study showed that data quality, internal consistency, and discriminative validity suggest that the five-point scale version should be used in future research [42]. In the questionnaire, the teachers were also asked to identify whether they mainly worked in a primary school (1st to 7th grade, age 6-13), a secondary school (age [14][15][16], or an upper secondary school (age 17-19).…”
Section: Methodsmentioning
confidence: 99%
“…Environmental changes comprise altered school settings with a new school location, new teachers, new subjects, and new classmates. Furthermore, biological changes relate to maturation and puberty occurring during the three years of secondary school (age [13][14][15]. This period of environmental and biological changes may affect social inclusion negatively.…”
Section: Inclusion Is Mostly Observed In Primary Schoolmentioning
confidence: 99%
See 1 more Smart Citation